The transfer of Dutch Delta Planning expertise to Bangladesh: A process of policy translation. Issue 104 (February 2020) - Hasan, Shahnoor; Evers, Jaap; Zwarteveen, Margreet
Abstract: Representatives of the Dutch government usually refer to the Bangladesh Delta Plan 2100 as an example of the successful transfer of the Dutch Delta Approach to Bangladesh. Their storyline aligns with theorizations of policy transfer as a process of diffusion. These ascribe the mobility of a policy – or its capacity to travel - to its intrinsic quality. The belief in the quality of the Dutch Delta Approach is anchored in the renowned Dutch ability to deal with its own floods and flood risks. By making the contents of that what travels an important cause of its mobility, diffusion theories make it difficult to see, acknowledge and understand the actions and actors needed to make policy transfer happen. This is why in this paper we theorize policy transfer as a process of translation. Based on an identification of the Dutch and Bangladeshi actors involved in the transfer of the Dutch Delta Approach to Bangladesh, and by re-tracing their actions, we show that the transfer entailed an active process of engagement, negotiation, and contestation. In their attempts to develop a Bangladeshi version of the Plan, the involved actors made active use of old relations of collaboration and friendship, while also developing new ones. In the course of the transfer process, and because of the negotiations and contestations that it entailed, the delta plan became something else altogether. The paper concludes that telling the story of the transfer of the Dutch Delta Approach as a story of translation is useful as it allows recognizing and giving credit not just to those who initiated the process, but to all involved. This, we hope, can in turn provide the basis for a more symmetrical dialogue between 'senders' and 'recipients' in international policy transfers.